The Organoleptic and Physicochemical Characteristic of Gelato by Fish Bone Gelatin Addition - Vinnoya Apcaresta Alika; Yoni Atma (Journal of Applied Sciences and Advanced Technology, 2018)
This study aims to determine the effect of fish bone gelatin addition on physical, chemical, and organoleptic characteristics of gelato. This research was done on three stages: fish bone gelatin extraction, gelato production and analysis. The treatment factor consists of concentration: 0%, 0.4%, 0.8% and 1.2% of fish bone gelatin additions. Data were analyzed by one way analysis of variant (ANOVA) at level 5% and then continued by Tukey HSD (Honestly Significant Different) test or Tukey’s range test. The result shown that fish bone gelatin addition has effect to organoleptic, physical, and chemical characteristics of gelato. The best concentration was 1.2% for fish bone gelatin addition. Gelato with concentration 1.2 % fish bone gelatin have texture, taste, colour, aroma and aftertaste range in netral until like slightly in organoleptic (hedonic) value range i.e between 2.62 until 3.70. This gelato have overrun, melting point and pH in 30.48%, 38.4 minutes and 6.6 respectively. It was contains 3.62% protein, 6.32% fat, and 15,62% sucrose. This nutrition contents was confirm with the Indonesian National for Standardization  (SNI) for ice cream groups.